2018
DOI: 10.3389/fpls.2018.00323
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Abscisic Acid Promotes Anthocyanin Biosynthesis and Increased Expression of Flavonoid Synthesis Genes in Vitis vinifera × Vitis labrusca Table Grapes in a Subtropical Region

Abstract: Hybrid (Vitis vinifera ×Vitis labrusca) table grape cultivars grown in the subtropics often fail to accumulate sufficient anthocyanins to achieve good uniform berry color. Growers of V. vinifera table grapes in temperate regions generally use ethephon and, more recently, (S)-cis-abscisic acid (S-ABA) to overcome this problem. The objective of this study was to determine if S-ABA applications at different timings and concentrations have an effect on anthocyanin regulatory and biosynthetic genes, pigment accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 52 publications
(79 reference statements)
12
66
0
2
Order By: Relevance
“…However, in 'Xiahei' grapes, after ABA treatment, the content of delphinidin did not change significantly, and only the content of anthocyanin increased significantly. This indicated that ABA and iso-PhABA may affect the content of different kinds of anthocyanin monomers in different grape cultivars, which was consistent with previous findings [32,33].…”
Section: Iso-phaba Improves the Anthocyanin Content In Grape Berriessupporting
confidence: 92%
“…However, in 'Xiahei' grapes, after ABA treatment, the content of delphinidin did not change significantly, and only the content of anthocyanin increased significantly. This indicated that ABA and iso-PhABA may affect the content of different kinds of anthocyanin monomers in different grape cultivars, which was consistent with previous findings [32,33].…”
Section: Iso-phaba Improves the Anthocyanin Content In Grape Berriessupporting
confidence: 92%
“…The up-regulations of TDR and eight genes ( CHS , F3H , F3′H , F3′5′H , DFR , ANS , UFGT , and OMT ) (Fig 7) might contribute to the anthocyanin accumulation (Table 2) and the associated fruit skin coloration (Fig 2 and Table 1). In ABA-treated grape [61], strawberry [12], and blueberry fruits [8], however, the levels of anthocyanin accumulation and its associated gene expression were dependent on the concentration, timing, and duration of the ABA application. Despite these differences, the transcription factors and genes were similarly expressed in those fruits during ripening [8, 12, 61, 62].…”
Section: Resultsmentioning
confidence: 99%
“…In ABA-treated grape [61], strawberry [12], and blueberry fruits [8], however, the levels of anthocyanin accumulation and its associated gene expression were dependent on the concentration, timing, and duration of the ABA application. Despite these differences, the transcription factors and genes were similarly expressed in those fruits during ripening [8, 12, 61, 62]. More detailed information on ABA effects under various environmental and experimental conditions is needed to understand the ripening process of naturally grown fruits and to explore the possible implementation of ABA application in agricultural fields.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with abscisic acid resulted in higher accumulation of anthocyanins in the skin of grapes and increased the expression of CHI, F3H, DFR, and UFGT biosynthetic enzymes and MYBA1 and MYBA2 transcription factors. 43 JAs have been found to affect color formation in pears and blueberries, possibly by increasing anthocyanin biosynthesis. 20,28 Interestingly, the application of indole-3-acetic acid has been found to inhibit MeJA-induced anthocyanin accumulation in red raspberries by suppressing the expression of MYB10 and ANS.…”
Section: Effects Of Pdj On Transcript Levels Of Anthocyanin Biosynthementioning
confidence: 99%